Inovasi Pembelajaran dalam Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Nabella Febrianti; Pritasari, Ade Cyntia (Tahta Media Group, 2024)
This study aims to investigate and analyze how learning innovation can serve as a solution to enhance student motivation in Elementary Schools (SD). The research explores various learning models and media employed to boost student learning motivation, including Problem-Based Learning (PBL), blended learning, digital learning, interactive learning, cooperative learning (STAD type), active learning (Index Card Match type), and guided inquiry models, as well as learning videos, linktree and wordwall applications, educational games, quizwhizzer and kinemaster applications, Kahoot, geocaching, technology-based animation, and snakes and ladders. The research employs a descriptive qualitative methodology with data collection techniques through a literature review. The literature sources used consist of journal articles published from 2015 to 2024 that are relevant to the research focus. The analysis reveals that digital learning media, specifically learning videos incorporating animation, are frequently utilized to enhance student motivation. These videos facilitate easier comprehension of the material for students. This research suggests that digital learning media in the classroom can be effectively implemented by teachers to enhance student motivation in Elementary Schools.